Commodity prices, growth, and the natural resource curse: reconciling a conundrum - Collier, P; Goderis, B (2007)
Currently, evidence on the ‘resource curse’ yields a conundrum. While there is much crosssection evidence to support the curse hypothesis, time series analyses using vector autoregressive (VAR) models have found that commodity booms raise the growth of commodity exporters. This paper adopts panel cointegration methodology to explore longer term effects than permitted using VARs. We find strong evidence of a resource curse. Commodity booms have positive short-term effects on output, but adverse long-term effects. The long-term effects are confined to “high-rent”, non-agricultural commodities. We also find that the resource curse is avoided by countries with sufficiently good institutions. We test the channels of the resource curse proposed in the literature and find that a substantial part of it is explained by high public and private consumption, low or inefficient total investment, and an overvalued exchange rate. Our results fully account for the cross-section results in the seminal paper by Sachs and Warner (1995).